Composite permeable membrane for water desalination and preparation method thereof

By introducing functional anchor groups into the composite permeable membrane for water desalination and constructing an embedded hydrophilic barrier layer and a nanocontainer-type bactericidal precursor layer, combined with real-time monitoring and modification regulation, the problem of anti-biological contamination of the composite permeable membrane is solved, and the service life and operational stability of the membrane are improved.

CN120733577AActive Publication Date: 2025-10-03SHENZHEN ENERGY RESOURCES COMPREHENSIVE DEV CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511110006.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-10-03
Estimated Expiration
2045-08-08

AI Technical Summary

Technical Problem

Existing composite osmotic membranes used for water desalination have insufficient resistance to biological fouling during long-term operation, resulting in decreased membrane flux, shortened service life and increased operating costs.

Method used

By activating and pretreating the reverse osmosis membrane base membrane, introducing functional anchor groups, and constructing an embedded hydrophilic barrier layer and a nanocontainer-type bactericidal precursor layer, combined with real-time monitoring and modification regulation, a multiple synergistic protection system is formed to achieve efficient and durable inhibition of different microorganisms.

Benefits of technology

It significantly improves the service life and operational stability of the membrane, achieves efficient and long-lasting inhibition of different microorganisms, and avoids damage to membrane performance and the risk of secondary pollution caused by excessive sterilization.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The preparation method comprises the following steps: carrying out activation pretreatment on a reverse osmosis membrane base membrane, and introducing a functional anchor point group on the surface of the membrane; a layered assembly mode is adopted, an embedded hydrophilic barrier layer and a nanometer container type sterilization precursor layer are sequentially constructed, and the nanometer container type sterilization precursor layer contains a controllable release structure capable of responding to microbial metabolites or external stimulation; and real-time monitoring and modification regulation are carried out in the layered assembly process. According to the technical scheme, through the design of a controllable release structure, the long-acting antibacterial performance is guaranteed, and the influence of excessive sterilization on the film performance is avoided. Meanwhile, the uniformity and integrity of the functional layer are ensured through real-time monitoring and modification regulation, the service life of the membrane is remarkably prolonged, the operation stability of the membrane is remarkably improved, and the method has important significance in reducing the operation cost of the system and preventing secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane material preparation for water treatment, in particular to a composite permeable membrane for water desalination and a preparation method thereof. Background Art

[0002] Composite permeable membranes for water desalination are polymer-based separation membrane materials that, through the application of pressure, allow water molecules to pass through while blocking salt and other impurities. These membranes typically consist of a multi-layered functional structure, including a porous base layer for mechanical support and a dense selective layer that determines separation performance. This composite structural design ensures both mechanical strength and excellent selective separation. Due to their unique separation mechanism and superior desalination performance, composite permeable membranes for water desalination have become one of the most promising core materials in the fields of seawater desalination and high-salinity wastewater treatment.

[0003] However, in actual application, composite permeable membranes face serious biological fouling problems. When microorganisms adhere to and reproduce on the membrane surface, a biofilm will gradually form. This biofilm will not only cause fouling and blockage on the membrane surface, resulting in a significant decrease in water production flux, but also increase the energy consumption of the system operation. More seriously, once the biofilm is formed, its metabolites may cause irreversible damage to the membrane material, significantly shortening the service life of the membrane. Although existing technologies have attempted to solve this problem by increasing the hydrophilicity of the membrane surface or introducing bactericidal materials, these methods often have obvious limitations: on the one hand, simple surface modification is difficult to achieve a long-lasting antibacterial effect, and the modified layer is prone to failure during use; on the other hand, traditional bactericidal material modification methods are difficult to take into account the broad-spectrum inhibitory effect on different types of microorganisms, and may affect the basic separation performance of the membrane. Under continuous operation conditions, the anti-biological fouling effect of these technical solutions is often unsatisfactory, resulting in the system needing to frequently shut down for cleaning or replacement of membrane components, which not only increases operating costs but also may bring the risk of secondary pollution. Therefore, how to achieve efficient and durable inhibition of different microorganisms while maintaining or improving membrane flux and retention performance has become a core issue that needs to be urgently addressed in this field. Summary of the Invention

[0004] The main purpose of the present invention is to solve the technical problem that the existing composite permeable membrane for water desalination has insufficient anti-biological pollution performance.

[0005] A first aspect of the present invention provides a method for preparing a composite permeable membrane for water desalination, the method comprising: The reverse osmosis membrane base film is pre-activated to introduce functional anchor groups on the membrane surface for hierarchical assembly of functional layers; The functional anchor groups are used for layered assembly to sequentially construct an embedded hydrophilic barrier layer and a nanocontainer-type bactericidal precursor layer on the surface of the activated membrane. The embedded hydrophilic barrier layer and the nanocontainer-type bactericidal precursor layer constitute a functional layer structure. The nanocontainer-type bactericidal precursor layer includes a controllable release structure that can respond to microbial metabolites or external stimuli to release antibacterial substances. During the layered assembly process, the membrane surface morphology and the construction status of the functional layer structure are monitored in real time, and the functional layer structure is modified and regulated according to the monitoring results to obtain a composite permeable membrane for water desalination.

[0006] Preferably, the activation pretreatment comprises: First, the reverse osmosis membrane base membrane is homogenously cleaned using a cleaning solution containing a chelating agent and a surfactant, combined with ultrasonic oscillation treatment; then, the elastic-plastic properties of the cleaned base membrane are regulated using a reversible crosslinking agent or a swelling agent; finally, functional anchor groups are introduced onto the surface of the reverse osmosis membrane base membrane by combining low-temperature plasma treatment and immersion in a precursor solution containing a silane compound.

[0007] Preferably, in the cleaning solution used for the homogeneous cleaning, ethylenediaminetetraacetic acid is used as the chelating agent, and the mass concentration of ethylenediaminetetraacetic acid is 0.01%-0.1%, and sodium dodecylbenzenesulfonate is used as the surfactant, and the mass concentration of sodium dodecylbenzenesulfonate is 0.005%-0.05%; The frequency of the ultrasonic oscillation treatment is 20-60kHz, and the time of the ultrasonic oscillation treatment is 10-30min; The elastic-plasticity control uses N-methylpyrrolidone as the swelling agent, the concentration of N-methylpyrrolidone is 10-30%, and the elastic-plasticity control time is 5-15 minutes; The power of the low-temperature plasma treatment is 30-100W, and the time of the low-temperature plasma treatment is 1-5 minutes; The silane compound is selected from one or a combination of 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane. The mass concentration of the silane compound in the precursor solution is 0.5%-2%, and the immersion time of the precursor solution is 30-60 minutes.

[0008] Preferably, the construction of the embedded hydrophilic barrier layer includes: A polymerizable monomer containing at least one hydrophilic group selected from betaine groups or sulfonic acid groups is selected, and the polymerizable monomer is prepared into an aqueous solution with a mass concentration of 1%-5%. In situ polymerization is carried out on the surface of the activated membrane by ultraviolet light-induced polymerization, so that the polymerizable monomer is chemically bonded to the functional anchor group to form a semi-interpenetrating network structure; wherein the wavelength of the ultraviolet light-induced polymerization is 280-400nm, and the time of the ultraviolet light-induced polymerization is 5-20min; the semi-interpenetrating network structure partially extends to the surface layer of the reverse osmosis membrane base membrane.

[0009] Preferably, the polymerizable monomer is selected from one or a combination of N,N-dimethyl-N-(2-methacryloyloxyethyl)-N-(3-sulfopropyl)ammonium inner salt, 2-methacryloyloxyethyltrimethylammonium chloride, N-(3-sulfopropyl)-N-methylacrylamide, and 2-acrylamido-2-methylpropanesulfonic acid; The ultraviolet light-induced polymerization further includes: adding a photoinitiator to the aqueous solution of the polymerizable monomer, wherein the photoinitiator is selected from one of benzophenone and 2,2-dimethoxy-2-phenylacetophenone, and the amount of the photoinitiator added is 0.1%-0.5% of the mass of the polymerizable monomer; the temperature of the ultraviolet light-induced polymerization is 25-35°C, and the intensity of the ultraviolet light is 10-30mW / cm².

[0010] Preferably, the construction of the nanocontainer-type sterilization precursor layer includes: A bactericidal active substance is encapsulated in carrier nanoparticles, wherein the bactericidal active substance is selected from one or more combinations of imidazole ionic liquids, pyridine ionic liquids, silver ions, copper ions, silver ion complexes, and copper ion complexes, and the carrier nanoparticles are selected from hollow silica nanoparticles or metal-organic framework nanoparticles; the particle size of the hollow silica nanoparticles is 50-200 nm, and the particle size of the metal-organic framework nanoparticles is 100-300 nm; the surface of the carrier nanoparticles encapsulating the bactericidal active substance is modified with polydopamine or polyethyleneimine to prepare a nanocontainer with a cross-linkable functional group; the mass fraction of the polydopamine is 5%-15% of the mass of the carrier nanoparticles, and the mass fraction of the polyethyleneimine is 3%-10% of the mass of the carrier nanoparticles; the nanocontainer is dispersed in an aqueous solution, and a nanocontainer-type bactericidal precursor layer with a controlled release structure is formed through chemical bonding with the surface of the embedded hydrophilic barrier layer.

[0011] Preferably, the release mechanism of the controlled release structure includes: When microorganisms multiply on the membrane surface, the metabolic products of the microorganisms cause changes in the local pH, redox potential or enzyme activity. The changes cause the surface modification layer of the nanocontainer to swell or dissolve, thereby achieving the spontaneous release of the bactericidal active substance; alternatively, by adding a hydrogen peroxide solution with a concentration of 0.001%-0.1% or a citric acid solution with a concentration of 0.05%-0.5% to the membrane system as an external trigger factor, the permeability of the surface modification layer of the nanocontainer is changed, thereby achieving the controlled release of the bactericidal active substance; wherein, when the local pH value drops to the range of 4.0-6.0, or the redox potential increases by 50-200mV, the surface modification layer begins to respond; the duration of the spontaneous release or controlled release is 2-24 hours.

[0012] Preferably, the real-time monitoring includes: During the layered assembly process, an online micro-spectrometer is used to detect spectral changes on the membrane surface, and the wavelength range of the spectral detection is 200-800nm; an electrochemical impedance meter is used to detect electrochemical impedance changes on the membrane surface, and the test frequency range of the electrochemical impedance is 0.01Hz-100kHz; based on the spectral changes and electrochemical impedance changes, the uniformity and integrity of the functional layer structure are judged; wherein, when the peak intensity change of the reflection spectrum on the membrane surface is detected to exceed ±10%, or the electrochemical impedance value deviates from the set value by ±20%, it is determined that the functional layer structure has local defects.

[0013] Preferably, the modification and regulation include: when local defects are detected in the functional layer structure, locally repairing the defective area by microfluid spraying, the working pressure of the microfluid spraying is 0.1-0.5 MPa, and the scanning speed of the microfluid spraying is 1-5 mm / s; when the surface electrical properties of the functional layer structure are detected to deviate from expectations, adding a regulating polyelectrolyte solution with a mass concentration of 0.01%-0.1% to the system for electrical regulation, the regulating polyelectrolyte is selected from one of polyacrylamide and polyvinyl pyrrolidone, and the regulation time is 10-30 min.

[0014] A second aspect of the present invention provides a composite permeable membrane for water desalination, which is prepared by the above-mentioned method for preparing a composite permeable membrane for water desalination.

[0015] The method for preparing composite permeable membranes for water desalination proposed in this paper aims to address the problem of membrane performance degradation caused by biofouling during long-term operation. Specifically, existing methods such as surface modification or biocidal material modification have difficulty achieving both a long-lasting antimicrobial effect and a broad-spectrum antibacterial effect. This not only affects the membrane's separation performance and service life, but also increases system operating costs and introduces the potential risk of secondary contamination.

[0016] The preparation method includes three steps: first, functional anchor groups are introduced into the surface of the reverse osmosis membrane base membrane through activation pretreatment; then, a layered assembly method is used to sequentially construct an embedded hydrophilic barrier layer and a nanocontainer-type bactericidal precursor layer, wherein the nanocontainer-type bactericidal precursor layer contains a controllable release structure that can respond to microbial metabolites or external stimuli; finally, real-time monitoring and modification and regulation are carried out during the layered assembly process.

[0017] The key to this preparation method's ability to effectively solve the problem of biological contamination is that it forms a multi-synergistic protection system. First, by introducing functional anchor groups on the surface of the base membrane, a stable binding site is provided for the subsequent functional layer, which ensures that the modified layer will not fall off and fail during use. Secondly, the embedded hydrophilic barrier layer forms a preliminary anti-fouling barrier that can effectively reduce the initial adhesion of microorganisms. More importantly, the nanocontainer-type bactericidal precursor layer achieves intelligent antibacterial control through a controlled release structure: when microbial reproduction is detected, its metabolites trigger the system to spontaneously release antibacterial substances; when enhanced sterilization is required, additional release can be triggered by external stimuli. This precise and controllable release mechanism not only ensures a sustained antibacterial effect, but also avoids damage to membrane performance due to excessive sterilization.

[0018] Furthermore, real-time monitoring and modification during the layered assembly process further enhances the reliability of the solution. By continuously monitoring the membrane surface morphology and the construction status of the functional layers and making timely adjustments, uneven distribution or localized defects in the functional layers are effectively prevented, ensuring the stable functioning of the entire protection system. This dynamic optimization approach significantly improves the membrane's service life and operational stability, ultimately achieving highly effective and long-lasting inhibition of diverse microorganisms. DETAILED DESCRIPTION

[0019] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0020] The present invention provides a method for preparing a composite permeable membrane for water desalination, comprising the following steps: The reverse osmosis membrane base film is pre-activated to introduce functional anchor groups on the membrane surface for hierarchical assembly of functional layers; The activation pretreatment comprises: First, the reverse osmosis membrane base membrane is homogenously cleaned using a cleaning solution containing a chelating agent and a surfactant, combined with ultrasonic oscillation treatment; then, the elastic-plastic properties of the cleaned base membrane are regulated using a reversible crosslinking agent or a swelling agent; finally, functional anchor groups are introduced onto the surface of the reverse osmosis membrane base membrane by combining low-temperature plasma treatment and immersion in a precursor solution containing a silane compound.

[0021] Specifically, homogenous cleaning is intended to remove trace metal ions and organic residues on the surface and inside of the base membrane. During the specific operation, the base membrane is immersed in a cleaning solution containing ethylenediaminetetraacetic acid and sodium dodecylbenzenesulfonate, and simultaneously oscillated in an ultrasonic cleaner. Ethylenediaminetetraacetic acid forms stable chelates with metal ions through its four carboxyl groups, thereby stripping the metal ions from the membrane surface; sodium dodecylbenzenesulfonate, relying on its hydrophilic and lipophilic properties, can effectively emulsify and disperse organic residues; and the cavitation effect generated by ultrasonic oscillation enhances the penetration of the cleaning solution into the membrane pores, accelerating the removal of impurities. In addition to ultrasonic oscillation, high-speed stirring or microfluidic flushing can also be used to assist the cleaning process.

[0022] Elastic-plastic regulation modulates the microstructure of the basement membrane through swelling. The cleaned basement membrane is immersed in an N-methylpyrrolidone solution. The N-methylpyrrolidone molecules penetrate between the polymer segments, causing localized swelling and moderate microscopic expansion of the polymer segments. During this process, the movement of the polymer segments is controlled, preventing complete dissolution while maintaining a certain degree of fluidity. This step can also utilize reversible crosslinkers such as epoxy resins to achieve elastic-plastic regulation through chemical crosslinking.

[0023] Anchor groups are introduced using a combination of physical activation and chemical modification. First, the base film surface is activated using a low-temperature plasma treatment apparatus. Plasma bombardment generates active free radicals on the membrane surface. The activated base film is then immersed in a solution of 3-mercaptopropyltrimethoxysilane or 3-aminopropyltriethoxysilane. The methoxy or ethoxy groups in the silane molecules hydrolyze and react with the hydroxyl groups on the membrane surface, exposing the thiol or amino groups to form functional anchor points. Alternatives to this step include surface activation methods such as UV grafting or ozone oxidation.

[0024] This preparation step achieves deep purification and structural optimization of the base membrane. Homogeneous cleaning ensures the intrinsic properties of the base membrane; elastic-plastic regulation maintains the integrity of the membrane structure while creating space for the implantation of functional groups; surface activation and silanization modification construct stable chemical bonding sites on the membrane surface. These sites not only have specific chemical activity but also maintain good spatial accessibility.

[0025] In the present invention, preferably, in the cleaning solution used for the homogeneous cleaning, ethylenediaminetetraacetic acid is used as the chelating agent, and the mass concentration of ethylenediaminetetraacetic acid is 0.01%-0.1%, and sodium dodecylbenzenesulfonate is used as the surfactant, and the mass concentration of sodium dodecylbenzenesulfonate is 0.005%-0.05%; The frequency of the ultrasonic oscillation treatment is 20-60kHz, and the time of the ultrasonic oscillation treatment is 10-30min; The elastic-plasticity control uses N-methylpyrrolidone as the swelling agent, the concentration of N-methylpyrrolidone is 10-30%, and the elastic-plasticity control time is 5-15 minutes; The power of the low-temperature plasma treatment is 30-100W, and the time of the low-temperature plasma treatment is 1-5 minutes; The silane compound is selected from one or a combination of 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane. The mass concentration of the silane compound in the precursor solution is 0.5%-2%, and the immersion time of the precursor solution is 30-60 minutes.

[0026] Specifically, in the homogenization cleaning step, the concentration of EDTA is selected to be 0.01%-0.1%, which is based on the coordination effect of EDTA with metal ions. When the concentration is lower than 0.01%, the number of chelating agent molecules is insufficient to effectively complex the metal ions on the membrane surface; when the concentration exceeds 0.1%, the excess chelating agent will interfere with the subsequent surface modification process. The concentration of sodium dodecylbenzenesulfonate is set at 0.005%-0.05%. Within this concentration range, the surfactant molecules can form a stable micelle structure in the aqueous solution, thereby effectively encapsulating and emulsifying organic pollutants.

[0027] The ultrasonic oscillation frequency is selected to be 20-60kHz, and the treatment time is 10-30 minutes. The cavitation effect generated in this frequency range has moderate energy, which can enhance the penetration of the cleaning solution without causing mechanical damage to the membrane structure. Treatment times under 10 minutes are prone to incomplete cleaning, while treatment times exceeding 30 minutes may cause microscopic cracks on the membrane surface.

[0028] For elastic-plastic control, the N-methylpyrrolidone concentration was set between 10% and 30%, and the control time was 5-15 minutes. N-methylpyrrolidone molecules have strong polarity and a moderate molecular size, allowing them to moderately penetrate between polymer segments within the selected concentration range. Concentrations below 10% result in minimal swelling, while concentrations above 30% cause excessive swelling. The control time was chosen based on the kinetics of the swelling process; a time window of 5-15 minutes allows for sufficient expansion of the polymer segments without dissolution.

[0029] Low-temperature plasma treatment uses a power of 30-100W for 1-5 minutes. Within this power range, the plasma energy is sufficient to generate active free radicals on the film surface without causing thermal damage to the material. Treatment times exceeding 5 minutes can lead to excessive oxidation, while treatment times below 1 minute may result in insufficient activation.

[0030] For silanization modification, 3-mercaptopropyltrimethoxysilane or 3-aminopropyltriethoxysilane is used at a concentration of 0.5%-2% and an immersion time of 30-60 minutes. In the molecular structure of these two silane compounds, the methoxy or ethoxy group at one end forms a stable Si-O covalent bond with the membrane surface after hydrolysis, while the mercapto or amino group at the other end provides an active site for subsequent functionalization. When the silane concentration is below 0.5%, the surface modification density is insufficient; when the concentration is above 2%, self-polymerization is likely to occur. An immersion time of 30-60 minutes ensures sufficient adsorption and reaction of the silane molecules on the membrane surface.

[0031] The functional anchor groups are used for layered assembly to sequentially construct an embedded hydrophilic barrier layer and a nanocontainer-type bactericidal precursor layer on the surface of the activated membrane. The embedded hydrophilic barrier layer and the nanocontainer-type bactericidal precursor layer constitute a functional layer structure. The nanocontainer-type bactericidal precursor layer includes a controllable release structure that can respond to microbial metabolites or external stimuli to release antibacterial substances. In the present invention, preferably, the construction of the embedded hydrophilic barrier layer includes: A polymerizable monomer containing at least one hydrophilic group selected from betaine groups or sulfonic acid groups is selected, and the polymerizable monomer is prepared into an aqueous solution with a mass concentration of 1%-5%. In situ polymerization is carried out on the surface of the activated membrane by ultraviolet light-induced polymerization, so that the polymerizable monomer is chemically bonded to the functional anchor group to form a semi-interpenetrating network structure; wherein the wavelength of the ultraviolet light-induced polymerization is 280-400nm, and the time of the ultraviolet light-induced polymerization is 5-20min; the semi-interpenetrating network structure partially extends to the surface layer of the reverse osmosis membrane base membrane.

[0032] Specifically, the construction process begins with the selection of polymerizable monomers containing betaine or sulfonic acid groups. These hydrophilic groups are structurally highly polar. Sulfonic acid groups form stable hydrogen-bonding networks with water molecules through SO₃⁻ groups, while betaine groups, through their zwitterionic structure, form a dense hydration layer in an aqueous environment. These monomers are then formulated into a 1%-5% aqueous solution, a concentration range that ensures sufficient diffusion of the monomer molecules onto the membrane surface while preventing self-aggregation due to excessive concentration.

[0033] The polymerization reaction is initiated by ultraviolet light with a wavelength of 280-400nm. This wavelength range effectively excites the photoinitiator to generate free radicals while avoiding photodegradation of the membrane matrix. During the polymerization period of 5-20 minutes, the monomer molecules undergo chain polymerization under the initiation of free radicals and chemically bond to the functional anchor groups on the membrane surface. The specific reaction mechanism is as follows: the photoinitiator absorbs the ultraviolet light energy to generate primary free radicals, which trigger addition polymerization of the monomer molecules. Simultaneously, some of the growing polymer chains undergo free radical coupling with the anchor groups, forming chemical bonds. This process can also be achieved through thermal initiation or redox initiation.

[0034] During the polymerization process, the surface layer of the basement membrane possesses a certain degree of segmental mobility due to the early elastic-plastic regulation. This allows some polymer chains to penetrate the membrane surface space and form an interpenetrating structure with the basement membrane macromolecular chains. This semi-interpenetrating network is tightly bound to the membrane surface through chemical bonding, and further enhances the interfacial bonding strength through physical entanglement.

[0035] In the present invention, preferably, the polymerizable monomer is selected from one or a combination of N,N-dimethyl-N-(2-methacryloyloxyethyl)-N-(3-sulfopropyl)ammonium inner salt, 2-methacryloyloxyethyltrimethylammonium chloride, N-(3-sulfopropyl)-N-methylacrylamide, and 2-acrylamido-2-methylpropanesulfonic acid; The ultraviolet light-induced polymerization further includes: adding a photoinitiator to the aqueous solution of the polymerizable monomer, wherein the photoinitiator is selected from one of benzophenone and 2,2-dimethoxy-2-phenylacetophenone, and the amount of the photoinitiator added is 0.1%-0.5% of the mass of the polymerizable monomer; the temperature of the ultraviolet light-induced polymerization is 25-35°C, and the intensity of the ultraviolet light is 10-30mW / cm².

[0036] Specifically, the selected polymerizable monomers include four compounds with different molecular structures. The molecular structure of N,N-dimethyl-N-(2-methacryloyloxyethyl)-N-(3-sulfopropyl)ammonium inner salt contains two hydrophilic groups, betaine and sulfonic acid, which enhance its hydration ability. The quaternary ammonium salt structure in 2-methacryloyloxyethyltrimethylammonium chloride forms a stable hydration layer. N-(3-sulfopropyl)-N-methylacrylamide and 2-acrylamido-2-methylpropanesulfonic acid enhance hydrophilicity through the synergistic effect of sulfonic acid and amide groups. These monomers all contain unsaturated double bonds, enabling free radical polymerization under UV light initiation.

[0037] During the UV-induced polymerization process, benzophenone or 2,2-dimethoxy-2-phenylacetophenone is used as a photoinitiator. These two photoinitiators have strong light absorption capabilities in the 280-400nm wavelength range. When the photoinitiator absorbs UV light energy, the carbonyl group in the molecule undergoes transitions, generating excited molecules, which then break down to produce primary free radicals. The amount of photoinitiator added is controlled within the range of 0.1%-0.5% of the monomer weight. This amount generates sufficient free radicals to initiate polymerization while avoiding chain transfer reactions that may be caused by excessive initiator.

[0038] The polymerization temperature is controlled within the range of 25-35°C, which ensures sufficient thermal mobility of the monomer and initiator molecules while avoiding the accelerated chain termination reaction caused by excessively high temperatures. The UV light intensity is set at 10-30mW / cm². Within this range, the system can maintain a stable free radical concentration, thus achieving a controllable polymerization process.

[0039] In the present invention, preferably, the construction of the nanocontainer type sterilization precursor layer includes: A bactericidal active substance is encapsulated in carrier nanoparticles, wherein the bactericidal active substance is selected from one or more combinations of imidazole ionic liquids, pyridine ionic liquids, silver ions, copper ions, silver ion complexes, and copper ion complexes, and the carrier nanoparticles are selected from hollow silica nanoparticles or metal-organic framework nanoparticles; the particle size of the hollow silica nanoparticles is 50-200 nm, and the particle size of the metal-organic framework nanoparticles is 100-300 nm; the surface of the carrier nanoparticles encapsulating the bactericidal active substance is modified with polydopamine or polyethyleneimine to prepare a nanocontainer with a cross-linkable functional group; the mass fraction of the polydopamine is 5%-15% of the mass of the carrier nanoparticles, and the mass fraction of the polyethyleneimine is 3%-10% of the mass of the carrier nanoparticles; the nanocontainer is dispersed in an aqueous solution, and a nanocontainer-type bactericidal precursor layer with a controlled release structure is formed through chemical bonding with the surface of the embedded hydrophilic barrier layer.

[0040] Specifically, the preparation process first selects imidazolium ionic liquids, pyridine ionic liquids, silver ions, copper ions, and their complexes as bactericidal active substances. These substances have different bactericidal mechanisms: ionic liquids achieve bactericidal effects by disrupting bacterial cell membranes; silver ions and copper ions exert their antibacterial effects by interfering with bacterial metabolic systems and destroying cell walls. Hollow silica nanoparticles or metal-organic framework nanoparticles are selected as carriers, both of which have unique structural characteristics. Hollow silica nanoparticles have a large internal storage space due to their core-shell structure, and the shell provides a controllable material diffusion channel. Metal-organic framework nanoparticles, with their regular pore structure and coordination sites, can effectively load the bactericidal substance.

[0041] The particle size of the carrier nanoparticles is controlled within a specific range: 50-200 nm for hollow silica nanoparticles and 100-300 nm for metal-organic framework nanoparticles. This size range was chosen based on two considerations: first, the particles have a large specific surface area, providing ample storage space; second, this size ensures uniform distribution of particles on the membrane surface without agglomeration.

[0042] After encapsulating the bactericidal active substance into the carrier nanoparticles, they are surface-modified with polydopamine or polyethyleneimine. Polydopamine, through its catechol groups, spontaneously polymerizes to form a dense coating while retaining active functional groups; polyethyleneimine, with its abundant amino groups, provides cross-linking sites. The dosage of polydopamine is 5%-15% of the carrier mass, and polyethyleneimine is 3%-10%. These ratios ensure that the modified layer is neither too thin, resulting in incomplete coverage, nor too thick, impairing the release of the bactericidal substance.

[0043] The modified nanocontainers are dispersed in an aqueous solution and bonded to the hydrophilic barrier layer through chemical bonding. Specifically, the catechol groups in the polydopamine-modified layer or the amino groups in the polyethyleneimine can undergo condensation or addition reactions with the active groups on the surface of the hydrophilic barrier layer, forming stable chemical bonds.

[0044] In the present invention, preferably, the release mechanism of the controlled release structure includes: When microorganisms multiply on the membrane surface, the metabolic products of the microorganisms cause changes in the local pH, redox potential or enzyme activity. The changes cause the surface modification layer of the nanocontainer to swell or dissolve, thereby achieving the spontaneous release of the bactericidal active substance; alternatively, by adding a hydrogen peroxide solution with a concentration of 0.001%-0.1% or a citric acid solution with a concentration of 0.05%-0.5% to the membrane system as an external trigger factor, the permeability of the surface modification layer of the nanocontainer is changed, thereby achieving the controlled release of the bactericidal active substance; wherein, when the local pH value drops to the range of 4.0-6.0, or the redox potential increases by 50-200mV, the surface modification layer begins to respond; the duration of the spontaneous release or controlled release is 2-24 hours.

[0045] Specifically, the controlled release structure in this preparation method is designed with two release mechanisms: spontaneous release and externally triggered release.

[0046] The spontaneous release mechanism is based on local environmental changes caused by microbial metabolic activity. When microorganisms multiply on the membrane surface, their metabolic processes produce a variety of acidic substances, causing a decrease in the local pH. Simultaneously, microbial respiration alters the local redox state, and some bacterial species secrete specific enzymes. These environmental changes interact with the surface modification layer of the nanocontainer: when the local pH drops to the range of 4.0-6.0, the phenolic hydroxyl groups in polydopamine become protonated, causing conformational changes in the molecular chain and swelling of the modification layer. An increase in the redox potential by 50-200 mV triggers the formation of quinone structures within the polydopamine network, altering the permeability of the modification layer.

[0047] The externally triggered release mechanism is achieved by adding chemical reagents at specific concentrations. When a 0.001%-0.1% hydrogen peroxide solution is added to the membrane system, the hydrogen peroxide molecules undergo a redox reaction with the catechol groups in polydopamine, loosening the structure of the modified layer. The addition of a 0.05%-0.5% citric acid solution alters the protonation level of the polyethyleneimine through acid-base interactions, causing the modified layer to swell.

[0048] The release duration is controlled within the 2-24 hour range. Within this time window, the bactericidal active substance is able to maintain an effective concentration while avoiding rapid depletion. Dynamic light scattering experiments showed that the release process exhibits typical diffusion-controlled characteristics, with a rapid release rate within the first 2 hours, followed by a gradual leveling off.

[0049] During the layered assembly process, the membrane surface morphology and the construction status of the functional layer structure are monitored in real time, and the functional layer structure is modified and regulated according to the monitoring results to obtain a composite permeable membrane for water desalination.

[0050] In the present invention, preferably, the real-time monitoring includes: During the layered assembly process, an online micro-spectrometer is used to detect spectral changes on the membrane surface, and the wavelength range of the spectral detection is 200-800nm; an electrochemical impedance meter is used to detect electrochemical impedance changes on the membrane surface, and the test frequency range of the electrochemical impedance is 0.01Hz-100kHz; based on the spectral changes and electrochemical impedance changes, the uniformity and integrity of the functional layer structure are judged; wherein, when the peak intensity change of the reflection spectrum on the membrane surface is detected to exceed ±10%, or the electrochemical impedance value deviates from the set value by ±20%, it is determined that the functional layer structure has local defects.

[0051] Specifically, real-time monitoring uses a combination of spectral detection and electrochemical impedance spectroscopy to dynamically track the construction process of the functional layer.

[0052] Spectral analysis utilizes an online micro-spectrometer, covering a wavelength range of 200-800 nm. This wavelength range is selected based on the optical properties of the functional layer: the 200-400 nm range reflects the absorption of aromatic groups and conjugated structures, while the 400-800 nm range reflects the scattering characteristics of the nanoparticles. When the functional layer is uniformly deposited, the reflectance spectrum exhibits regular intensity variations; however, if local defects are present, the peak intensity of the reflectance spectrum will shift significantly.

[0053] Electrochemical impedance spectroscopy (EIS) testing uses a frequency sweep method with a test range of 0.01Hz-100kHz. In the high-frequency region (1-100kHz), the impedance response primarily reflects the capacitive properties of the functional layer, useful for assessing layer thickness uniformity. The low-frequency region (0.01-1Hz) reflects interfacial mass transfer processes and can be used to determine the density of the functional layer. Detailed information about the functional layer structure can be obtained by analyzing the real and imaginary parts of the impedance spectrum.

[0054] The criteria for determining performance are based on two thresholds: a change in the peak intensity of the film's surface reflectance spectrum exceeding ±10%, or a deviation of the electrochemical impedance value from a set value by ±20%. A ±10% variation in the reflectance spectrum indicates acceptable thickness fluctuations in the functional layer; a ±20% variation in the impedance value corresponds to the normal fluctuation range of the functional layer structure. Exceeding these thresholds indicates possible defects in the functional layer, such as breakage, detachment, or accumulation.

[0055] In the present invention, preferably, the modification and regulation include: when local defects are detected in the functional layer structure, locally repairing the defective area by microfluid spraying, the working pressure of the microfluid spraying is 0.1-0.5 MPa, and the scanning speed of the microfluid spraying is 1-5 mm / s; when the surface electrical properties of the functional layer structure are detected to deviate from expectations, adding a regulating polyelectrolyte solution with a mass concentration of 0.01%-0.1% to the system for electrical regulation, the regulating polyelectrolyte is selected from one of polyacrylamide and polyvinyl pyrrolidone, and the regulation time is 10-30 min.

[0056] Specifically, microfluidic spraying technology is used to repair local defects. This technology achieves targeted repair of defective areas through precisely controlled spraying parameters: the operating pressure is set within the range of 0.1-0.5MPa. Within this pressure range, the sprayed droplet size is controlled at 20-50 microns, which can accurately fill the defect location without affecting the surrounding area; the scanning speed is controlled at 1-5mm / s. This speed range ensures that the repair material can fully penetrate the defect area and interact with the original functional layer.

[0057] Surface electrical properties are regulated using polyelectrolyte regulation. When a deviation in the surface electrical properties of the functional layer is detected, a regulating polyelectrolyte solution at a concentration of 0.01%-0.1% is added to the system. The polyacrylamide or polyvinylpyrrolidone used exhibits specific molecular structural characteristics: polyacrylamide forms hydrogen bonds with the functional layer through its amide groups, while polyvinylpyrrolidone forms coordination with the functional layer through its pyrrolidone rings. These interactions enable the polyelectrolyte molecules to form a stable regulating layer on the surface of the functional layer.

[0058] The regulation time is set to 10-30 minutes. This time range is based on the adsorption kinetics of the polyelectrolyte on the surface of the functional layer: the first 10 minutes are mainly for rapid adsorption to establish the initial regulation effect; the next 20 minutes are used for the rearrangement of the molecular chains and conformational adjustment to achieve stable surface electrical properties.

[0059] Through this precise modification and regulation, effective repair of structural defects in the functional layer is achieved.

[0060] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformation made by using the description of the present invention under the inventive concept of the present invention, or directly / indirect application in other related technical fields, is included in the patent protection scope of the present invention.

Claims

1. A method for preparing a composite permeable membrane for water desalination, characterized in that: include: The reverse osmosis membrane base film is pre-activated to introduce functional anchor groups on the membrane surface for hierarchical assembly of functional layers; The functional anchor groups are used for layered assembly to sequentially construct an embedded hydrophilic barrier layer and a nanocontainer-type bactericidal precursor layer on the surface of the activated membrane. The embedded hydrophilic barrier layer and the nanocontainer-type bactericidal precursor layer constitute a functional layer structure. The nanocontainer-type bactericidal precursor layer includes a controllable release structure that can respond to microbial metabolites or external stimuli to release antibacterial substances. During the layered assembly process, the membrane surface morphology and the construction status of the functional layer structure are monitored in real time, and the functional layer structure is modified and regulated according to the monitoring results to obtain a composite permeable membrane for water desalination.

2. The method for preparing a composite permeable membrane for water desalination according to claim 1, wherein: The activation pretreatment comprises: First, the reverse osmosis membrane base membrane is homogenously cleaned using a cleaning solution containing a chelating agent and a surfactant, combined with ultrasonic oscillation treatment; then, the elastic-plastic properties of the cleaned base membrane are regulated using a reversible crosslinking agent or a swelling agent; finally, functional anchor groups are introduced onto the surface of the reverse osmosis membrane base membrane by combining low-temperature plasma treatment and immersion in a precursor solution containing a silane compound.

3. The method for preparing a composite permeable membrane for water desalination according to claim 2, wherein: In the cleaning solution used for the homogeneous cleaning, ethylenediaminetetraacetic acid is used as the chelating agent, and the mass concentration of ethylenediaminetetraacetic acid is 0.01%-0.1%, and sodium dodecylbenzenesulfonate is used as the surfactant, and the mass concentration of sodium dodecylbenzenesulfonate is 0.005%-0.05%; The frequency of the ultrasonic oscillation treatment is 20-60kHz, and the time of the ultrasonic oscillation treatment is 10-30min; The elastic-plasticity control uses N-methylpyrrolidone as the swelling agent, the concentration of N-methylpyrrolidone is 10-30%, and the elastic-plasticity control time is 5-15 minutes; The power of the low-temperature plasma treatment is 30-100W, and the time of the low-temperature plasma treatment is 1-5 minutes; The silane compound is selected from one or a combination of 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane. The mass concentration of the silane compound in the precursor solution is 0.5%-2%, and the immersion time of the precursor solution is 30-60 minutes.

4. The method for preparing a composite permeable membrane for water desalination according to claim 1, wherein: The construction of the embedded hydrophilic barrier layer includes: A polymerizable monomer containing at least one hydrophilic group selected from betaine groups or sulfonic acid groups is selected, and the polymerizable monomer is prepared into an aqueous solution with a mass concentration of 1%-5%. In situ polymerization is carried out on the surface of the activated membrane by ultraviolet light-induced polymerization, so that the polymerizable monomer is chemically bonded to the functional anchor group to form a semi-interpenetrating network structure; wherein the wavelength of the ultraviolet light-induced polymerization is 280-400nm, and the time of the ultraviolet light-induced polymerization is 5-20min; the semi-interpenetrating network structure partially extends to the surface layer of the reverse osmosis membrane base membrane.

5. The method for preparing a composite permeable membrane for water desalination according to claim 4, wherein: The polymerizable monomer is selected from one or more of N,N-dimethyl-N-(2-methacryloyloxyethyl)-N-(3-sulfopropyl)ammonium inner salt, 2-methacryloyloxyethyltrimethylammonium chloride, N-(3-sulfopropyl)-N-methylacrylamide, and 2-acrylamido-2-methylpropanesulfonic acid; The ultraviolet light-induced polymerization further includes: adding a photoinitiator to the aqueous solution of the polymerizable monomer, wherein the photoinitiator is selected from one of benzophenone and 2,2-dimethoxy-2-phenylacetophenone, and the amount of the photoinitiator added is 0.1%-0.5% of the mass of the polymerizable monomer; the temperature of the ultraviolet light-induced polymerization is 25-35°C, and the intensity of the ultraviolet light is 10-30mW / cm².

6. The method for preparing a composite permeable membrane for water desalination according to claim 1, wherein: The construction of the nano-container type sterilization precursor layer includes: A bactericidal active substance is encapsulated in carrier nanoparticles, wherein the bactericidal active substance is selected from one or more combinations of imidazole ionic liquids, pyridine ionic liquids, silver ions, copper ions, silver ion complexes, and copper ion complexes, and the carrier nanoparticles are selected from hollow silica nanoparticles or metal-organic framework nanoparticles; the particle size of the hollow silica nanoparticles is 50-200 nm, and the particle size of the metal-organic framework nanoparticles is 100-300 nm; the surface of the carrier nanoparticles encapsulating the bactericidal active substance is modified with polydopamine or polyethyleneimine to prepare a nanocontainer with a cross-linkable functional group; the mass fraction of the polydopamine is 5%-15% of the mass of the carrier nanoparticles, and the mass fraction of the polyethyleneimine is 3%-10% of the mass of the carrier nanoparticles; the nanocontainer is dispersed in an aqueous solution, and a nanocontainer-type bactericidal precursor layer with a controlled release structure is formed through chemical bonding with the surface of the embedded hydrophilic barrier layer.

7. The method for preparing a composite permeable membrane for water desalination according to claim 6, wherein: The release mechanism of the controlled release structure includes: When microorganisms multiply on the membrane surface, the metabolic products of the microorganisms cause changes in the local pH, redox potential or enzyme activity. The changes cause the surface modification layer of the nanocontainer to swell or dissolve, thereby achieving the spontaneous release of the bactericidal active substance; alternatively, by adding a hydrogen peroxide solution with a concentration of 0.001%-0.1% or a citric acid solution with a concentration of 0.05%-0.5% to the membrane system as an external trigger factor, the permeability of the surface modification layer of the nanocontainer is changed, thereby achieving the controlled release of the bactericidal active substance; wherein, when the local pH value drops to the range of 4.0-6.0, or the redox potential increases by 50-200mV, the surface modification layer begins to respond; the duration of the spontaneous release or controlled release is 2-24 hours.

8. The method for preparing a composite permeable membrane for water desalination according to claim 1, wherein: The real-time monitoring includes: During the layered assembly process, an online micro-spectrometer is used to detect spectral changes on the membrane surface, and the wavelength range of the spectral detection is 200-800nm; an electrochemical impedance meter is used to detect electrochemical impedance changes on the membrane surface, and the test frequency range of the electrochemical impedance is 0.01Hz-100kHz; based on the spectral changes and electrochemical impedance changes, the uniformity and integrity of the functional layer structure are judged; wherein, when the peak intensity change of the reflection spectrum on the membrane surface is detected to exceed ±10%, or the electrochemical impedance value deviates from the set value by ±20%, it is determined that the functional layer structure has local defects.

9. The method for preparing a composite permeable membrane for water desalination according to claim 8, wherein: The modification and regulation include: when local defects are detected in the functional layer structure, locally repairing the defective area by microfluid spraying, the working pressure of the microfluid spraying is 0.1-0.5MPa, and the scanning speed of the microfluid spraying is 1-5mm / s; when the surface electrical properties of the functional layer structure are detected to deviate from expectations, adding a regulating polyelectrolyte solution with a mass concentration of 0.01%-0.1% to the system for electrical property regulation, the regulating polyelectrolyte is selected from one of polyacrylamide and polyvinylpyrrolidone, and the regulation time is 10-30min.

10. A composite permeable membrane for water desalination, characterized in that: The composite permeable membrane for water desalination is prepared by the method for preparing the composite permeable membrane for water desalination according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for treating scrapped PVDF membrane by recycling water

    CN112999881A

  • Preparation method of antibacterial film

    CN119215675A

  • Carrier material with photoresponse controlled release function, preparation method of carrier material and application of carrier material in bio-based active packaging

    CN119371677A

  • A high permeability reverse osmosis membrane and preparation method thereof

    CN119771173A

  • A method for preparing modified ultrafiltration membrane

    CN119771174A